ON THE BEHAVIOR OF SOLUTIONS FOR A SYSTEM OF MULTIDIMENSIONAL HEAT TRANSFER EQUATIONS WITH NONLINEAR BOUNDARY CONDITIONS - Rakhmonov Z.R; Urolov G’.B (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Consider the following nonlinear system of parabolic equations coupled via nonlinear boundary conditions